(untitled) (International journal of artificial intelligence, 2026)
This article highlights the theoretical foundations, didactic possibilities, and practical significance of using mathematical modeling technology in the process of teaching natural sciences. Through mathematical modeling, the development of students’ logical thinking, analytical skills, problem-solving abilities, and interdisciplinary integration is scientifically substantiated. The article also presents examples of applying mathematical modeling technology in teaching biology, physics, and chemistry.